Genetics: Analysis of genes and genomes - Hartl, Daniel L.; Cochrane, Bruce J.; Cochrane, Bruce J. (Burlington, Jones & Bartlett Learning, 2019)
Genetics: Analysis of Genes and Genomes is a resource uniquely suited for learning and applying genetics to our world. Its DNA first presentation frames the discussion of genetics in modern terms, which provides the user the context to then understand its Mendelian history. Genetics continues to treat transmission genetics, molecular genetics, and evolutionary genetics as fully integrated subjects and provides students with an unprecedented understanding of the basic process of gene transmission, mutation, expression, and regulation. A new unit structure with self-contained chapters provides the flexibility to fit any course design, whether it be Mendel-early, Chromosome-early, or a Genome-first approach. The dynamism of genetics is also perfectly captured, as coverage of technological advances is woven together with ethical controversies. Problem-solving is a core element to this experimental discipline, and the ninth edition of Genetics is unparalleled in the tools it provides to unlock this fascinating subject. This rich resource allows students copious opportunities to practice and learn by using the clearly-presented mathematical concepts and exercises and chapter problems that encourage students to analyze and apply new skills.
Appendix 759-776p.; Index 808-829p.
Keywords: Gene expression; Transmission genetics; Variation; Botany